Klipplel-Trénaunay-Weber syndrome: A case report - Melo de Brito Costa Edja Maria; Boechat do Carmo Silva Fabricio; Coutinho Silva Cláudia Ana; Silveira Cardoso Abel; Leite Cavalcanti Alessandro (Serbian Medical Society - Dental Section, Belgrade, 2009)
Klippel-Trénaunay-Weber Syndrome (KTWS) is a rare congenital malformation that may include port-wine stain, soft tissue and bony hypertrophy, and venous malformations and lymphatic abnormalities. The oral findings include an enlarged maxilla, gingival enlargement, malocclusion and premature tooth eruption. This report describes a case of gingival enlargement in an 8-year-old male child with KTWS. The extraoral clinical examination revealed discrete hemifacial hypertrophy on the left side and hyperpigmented spots on the anterior region of the neck, left arm and left leg. The intraoral clinical examination showed a deep palate and enlarged buccal and palatal gingiva in the anterior maxilla. Complete blood count and all general medical examinations showed values within normal range while the psychological evaluation indicated a mild learning delay. Although it rarely involves the orofacial region, KTWS should be included in the differential diagnosis of severe gingival enlargement. In view of the potentially dangerous complications that can arise, it is imperative the dental surgeon has a thorough knowledge of this condition and its management.